PRINSIP KESANTUNAN BERBAHASA DALAM INTERAKSI ANTARA PEDAGANG DAN PEMBELI DI PASAR TENGAH ANJUNGAN - Anggela Rigarrani; Agus Syahrani; Mellisa Jupitasari (Universitas Tanjungpura, 2021)
AbstractThis study aims to describe the principles of politeness in the Central Market of Anjungan which include compliance with the principles of politeness, language deviation, and implementation of Bahasa Indonesian in schools according to the 2013 curriculum. The form of research used is qualitative with descriptive methods. Sources of data in this study are traders and buyers located at the Central Market of Anjungan. The data collection techniques used were listening techniques which had basic techniques (tapping technique), advanced techniques (listening technique without engaging proficiently), advanced techniques (recording technique), and advanced techniques (note technique). Techniques for checking the validity of data are peer examination and observation conditions. Based on the data analysis, it was found that there were 115 data on the principles of politeness, which were divided into obedience data and 40 deviation data. This study describes the lesson plan that will be carried out in school with Bahasa Indonesia RPP curriculum 2013 even semester class X regarding the negotiating text.Keyword: Politeness Principle, Politeness, Market, Anjongan District